Utilization of Cricket (Gryllus bimaculatus), Black Soldier Fly (Hermetia illucens), Mealworm (Tenebrio molitor), and Silkworm (Samia ricini dan Bombyx mori) as Alternative Feed Protein Sources - Agustin Herliatika; Dika Permatahati; Yusti Pujiawati; Gresy Eva Tresia; Elizabeth Wina (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2021)
The insect which contains high protein is potential to be used as an unconventional protein source (UPS) in feed. Production cost of this feedstuff is affordable through utilization of waste as growing media. Moreover, this production helps the environment by reducing the unprocessed waste. This study aims to review the potential use of cricket, black soldier fly (BSF), mealworm, and silkworm as UPS in replacing fish meal (FM) and soybean meal (SM) in the feed. The insect meal contains relative similar crude protein but higher ether-extract compared to conventional protein sources. The insect meal contains higher tyrosine but lower arginine, histidine, lysine, and tryptophan compared to FM and SM. The chitin content in UPS decreases the digestibility, causing restriction its utilization in the diet. However, it can be used as antibacterial and antifungal in feed, and in ruminant, it can be used to mitigate enteric methane emission. UPS in layer and broiler diet can replace SM, meanwhile, in quail diet, it can replace FM. From different sources, it can be summarised that the potential addition of BSF, cricket, mealworm, and silkworm in the broiler’s diet is 8%DM replacing 100% SM, 5-15%DM replacing 40-100% FM, 5-29,5%DM replacing 3-100% SM, and 7,8%DM replacing 100% SM, respectively. The potential addition of BSF and mealworm in the layer’s diet is 10-15%DM replacing 66-100% SM and 2-5%DM replacing 21% SM, respectively. The potential addition of cricket, mealworm, and silkworm in the quail’s diet is 2-8%DM replacing 25-100% FM, 2,25%DM replacing 25% FM, and 2,08-6,25%DM replacing 26-76% FM, respectively.